2019
DOI: 10.1186/s12937-019-0500-0
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validity of skin carotenoid status as a concentration biomarker of vegetable and fruit intake compared to multiple 24-h recalls and plasma carotenoid concentrations across one year: a cohort study

Abstract: BackgroundBiological markers of vegetable and fruit (VF) intake are needed both for nutrition surveillance and for the evaluation of nutrition interventions. Optically assessed skin carotenoid status (SCS) has been proposed as a marker of intake but there are few published validity studies to date. Therefore, the objective of the study was to examine the concurrent validity of multiple methods of assessing VF intake cross-sectionally and seasonally over one year and to discuss the relative merits and limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 47 publications
5
40
1
Order By: Relevance
“…Skin carotenoid levels measured in this study were positively correlated with serum total carotenoid concentrations ( Table 2 ). The correlation coefficient was high (0.678) and was comparable to that reported by Jahns et al (0.70) [ 16 ] and Meinke et al (0.6672) [ 19 ] although the measurement of our study was once per person and it contained some uncertainty. This suggests that skin carotenoid levels may be noninvasive measurable indicators of total serum carotenoid concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Skin carotenoid levels measured in this study were positively correlated with serum total carotenoid concentrations ( Table 2 ). The correlation coefficient was high (0.678) and was comparable to that reported by Jahns et al (0.70) [ 16 ] and Meinke et al (0.6672) [ 19 ] although the measurement of our study was once per person and it contained some uncertainty. This suggests that skin carotenoid levels may be noninvasive measurable indicators of total serum carotenoid concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…We speculate that we had a low correlation coefficient owing to limitations due to the uncertainty inherent in the dietary frequency method of the BDHQ [ 30 ], although this method has been validated. Jahns et al [ 19 ] reported that the correlation coefficients between skin carotenoid levels measured via RS and 24-h recall vegetable and fruit intake were 0.27 (not significant) and 0.37 ( p < 0.01), respectively, for baseline across the year, showing similar values to the coefficient of the present results. As green and yellow vegetables contain abundant carotenoids, the correlation coefficient between them was the highest in the present study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The Veggie Meter® uses pressure-mediated re ection spectroscopy on the index nger to assess skin carotenoids, which is a valid method to assess skin carotenoid status and approximate FV intake. 28,29 Three measurements were taken, and the mean of all measures was used in analysis.…”
Section: Skin Carotenoid Measurementmentioning
confidence: 99%
“…As an alternative, skin carotenoids measured with pressuremediated re ection spectroscopy is a validated method to approximate FV intake. [27][28][29] In this paper, we explored associations between self-reported and objectively-measured FV intake and three measures of farmers' market shopping behavior: (1) monthly frequency of farmers' market shopping, (2) variety of FV purchased on one market day, and (3) money and/or bene ts typically spent on FV at the farmers' market per week, in both a rural population and a racially/ethnically diverse urban population. We hypothesized that FV intake, measured both by self-report and skin carotenoids, would be positively associated with shopping frequency at farmers' markets, variety of FV purchased, and money and/or bene ts spent on FV.…”
Section: Introductionmentioning
confidence: 99%